Transmigration of intrauterine contraceptive devices: embedded in urinary bladder wall in pregnant woman - Mavintop, Prajna K.; Kumar, Ramesh; G. S., Sneha (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2022)
Globally, 14% of reproductive aged women use intrauterine contraception. The five intrauterine contraceptive devices (IUCDs) currently approved are chemically active and continually elute either copper or levonorgestrel. Uterine perforation is most serious and rare complication which can be acute or chronic in nature. Although uncommon, uterine embedment and perforation can occur. We report case of transmigration of intrauterine contraceptive device into the urinary bladder wall perforating the uterine wall in 25-year-old gravid female. She was subjected to ultrasound abdomen and pelvis which unveiled the diagnosis of migrated copper-T. Under spinal anaesthesia, laparotomy was done and IUCD was removed.